Corporate failure prediction : an investigation of PN4 companies / Wan Adibah Wan Ismail ... [et al.] - Wan Ismail, Wan Adibah; Raja Ahmad, Raja Adzrin; Kamarudin, Khairul Anuar; Yahaya, Rusliza (Faculty of Accountancy, 2005)
This paper investigates twenty financial ratios to develop a local financial failures prediction model. The study covers the period of 1993- 2001. We used mean and comparison of difference to the data set of five years before the failures to identify the most superlative ratios. From these ratios, we developed two prediction models by using a logistic regression. The results indicate that these models are excellent in predicting financial failures a year before failure. Both models are able to predict financial failure two years before the failures with more than 90% accuracy rate. It is hoped that this study, which is conducted using a recent data can contribute towards existing literatures on corporate failure prediction.